Magnesium Isoglycyrrhizinate Induces an Inhibitory Effect on Progression and Epithelial–Mesenchymal Transition of Laryngeal Cancer via the NF-κB/Twist Signaling - Zhang J; Zhao R; Xing D; Cao J; Guo Y; Li L; Sun Y; Tian L; Liu M (Drug Design, Development and Therapy, 2020)
Jiarui Zhang, Rui Zhao, Dongliang Xing, Jing Cao, Yan Guo, Liang Li, Yanan Sun, Linli Tian, Ming Liu Department of Otorhinolaryngology, Head and Neck Surgery, The Second Affiliated Hospital, Harbin Medical University, Harbin City, Heilongjiang Province 150086, People’s Republic of ChinaCorrespondence: Linli Tian; Ming LiuDepartment of Otorhinolaryngology, Head and Neck Surgery, The Second Affiliated Hospital, Harbin Medical University, No. 148 Baojian Road, Nangang District, Harbin City, Heilongjiang Province 150086, People’s Republic of ChinaEmail zt0675@163.com; qr9830@163.comBackground: Magnesium isoglycyrrhizinate (MI) was extracted from roots of the plant Glycyrrhiza glabra, which displays multiple pharmacological activities such as anti-inflammation, anti-apoptosis, and anti-tumor. Here, we aimed to investigate the effect of MI on the progression and epithelial–mesenchymal transition (EMT) of laryngeal cancer.Methods: Forty laryngeal cancer clinical samples were used. The role of MI in the proliferation of laryngeal cancer cells was assessed by MTT assay, Edu assay and colony formation assay. The function of MI in the migration and invasion of laryngeal cancer cells was tested by transwell assays. The effect of MI on apoptosis of laryngeal cancer cells was determined by cell apoptosis assay. The impact of MI on tumor growth in vivo was analyzed by tumorigenicity analysis using Balb/c nude mice. qPCR and Western blot analysis were performed to measure the expression levels of gene and protein, respectively.Results: We identified that EMT-related transcription factor Twist was significantly elevated in the laryngeal cancer tissues. The expression of Twist was also enhanced in the human laryngeal carcinoma HEP-2 cells compared with that in the primary laryngeal epithelial cells. The high expression of Twist was remarkably correlated with poor overall survival of patients with laryngeal cancer. Meanwhile, our data revealed that MI reduced cell proliferation, migration and invasion and enhanced apoptosis of laryngeal cancer cells in vitro. Moreover, MI decreased transcriptional activation and the expression levels of NF-κB and Twist, and alleviated EMT in vitro and in vivo. MI remarkably inhibited tumor growth and EMT of laryngeal cancer cells in vivo.Conclusion: MI restrains the progression of laryngeal cancer and induces an inhibitory effect on EMT in laryngeal cancer by modulating the NF-κB/Twist signaling. Our finding provides new insights into the mechanism by which MI inhibits laryngeal carcinoma development, enriching the understanding of the anti-tumor function of MI.Keywords: laryngeal cancer, progression, EMT, magnesium isoglycyrrhizinate, Twist, NF-κB signaling